Efficiency determination of induction motor and its sensitivity analysis towards parameter variation. (1st January 2014) - Chandrakanth, S. Anil; Chelliah, Thanga Raj; Srivastava, S.P.
The exact knowledge of some of the induction motor parameters is very important to implement efficient control schemes and to determine the efficiency. These parameters can be obtained by no-load test that is not easily possible for the motors working in process industries where continuous operation is required. Here, particle swarm optimisation is used for in situ efficiency determination of induction motor (5 hp) without performing no-load test. The part load efficiency and power factor can be improved through loss model controller where the motor excitation is adjusted in accordance with load and speed. Induction motor parameters vary with temperature. So, parameters obtained by conducting no load and blocked rotor test may vary with loading of induction motor. LMC is sensitive to parameter variation and its performance is affected when parameters change. An attempt is made to gain a deeper physical insight into the induction motor operation through sensitivity analysis of its equivalent circuit parameters. This study reveals the effect each of the circuit parameters namely Rs, Rr, Ls, Lr and Lm has on torque, speed, flux and DC-link power, respectively.